Legal aspects of commentary - Gabor, Dominik (The Opole Studies in Administration and Law, 2022)
Commentary's work is one of the current trends in the Polish Internet. More and more Internet users start their adventure by creating materials that comment, discuss and sometimes stigmatize the behavior of other Internet users – especially influencers. The article discusses the key, in the author's opinion, legal problems resulting from the type of creativity, which are commentary-type materials. The study analyzes copyright issues in the form of the right to quote, protection of personal rights - honor and good name, criminal law - defamation, and the secrecy of information sources. The article also provides practical advice for commentary practitioners to facilitate their online activities.